The Effect of Rhodamine-Derived Superparamagnetic Maghemite Nanoparticles on the Motility of Human Mesenchymal Stem Cells and Mouse Embryonic Fibroblast Cells - Baiazitova, Larisa (Molecules, 2019)
Nanoparticles have become popular in life sciences in the last few years. They have been produced in many variants and have recently been used in both biological experiments and in clinical applications. Due to concerns over nanomaterial risks, there has been a dramatic increase in investigations focused on safety research. The aim of this paper is to present the advanced testing of rhodamine-derived superparamagnetic maghemite nanoparticles (SAMN-R), which are used for their nontoxicity, biocompatibility, biodegradability, and magnetic properties. Recent results were expanded upon from the basic cytotoxic tests to evaluate cell proliferation and migration potential. Two cell types were used for the cell proliferation and tracking study: mouse embryonic fibroblast cells (3T3) and human mesenchymal stem cells (hMSCs). Advanced microscopic methods allowed for the precise quantification of the function of both cell types. This study has demonstrated that a dose of nanoparticles lower than 20 µg·cm(−2) per area of the dish does not negatively affect the cells’ morphology, migration, cytoskeletal function, proliferation, potential for wound healing, and single-cell migration in comparison to standard CellTracker™ Green CMFDA (5-chloromethylfluorescein diacetate). A higher dose of nanoparticles could be a potential risk for cytoskeletal folding and detachment of the cells from the solid extracellular matrix.